Neurocysticercosis, familial cerebral cavernomas and intracranial calcifications: differential diagnosis for adequate management - Emerson Leandro Gasparetto; Soniza Alves-Leon; Flavio Sampaio Domingues; João Thiago Frossard; Selva Paraguassu Lopes; Jorge Marcondes de Souza (Arquivos de Neuro-Psiquiatria)
ABSTRACT Neurocysticercosis (NCC) is an endemic disease and important public health problem in some areas of the World and epilepsy is the most common neurological manifestation. Multiple intracranial lesions, commonly calcified, are seen on cranial computed tomography (CT) in the chronic phase of the disease and considered one of the diagnostic criteria of the diagnosis. Magnetic resonance imaging (MRI) is the test that better depicts the different stages of the intracranial cysts but does not show clearly calcified lesions. Cerebral cavernous malformations (CCM), also known as cerebral cavernomas, are frequent vascular malformations of the brain, better demonstrated by MRI and have also epilepsy as the main form of clinical presentation. When occurring in the familial form, cerebral cavernomas typically present with multiple lesions throughout the brain and, very often, with foci of calcifications in the lesions when submitted to the CT imaging. In the countries, and geographic areas, where NCC is established as an endemic health problem and neuroimaging screening is done by CT scan, it will be important to consider the differential diagnosis between the two diseases due to the differences in adequate management.